Changes in Pro-Inflammatory Markers in Detoxifying Chronic Alcohol Abusers, Divided by Lesch Typology, Reflect Cognitive Dysfunction. (4th July 2017) - Hanak, Catherine; Benoit, Janaina; Fabry, Lauriane; Hein, Matthieu; Verbanck, Paul; de Witte, Philippe; Walter, Henriette; Dexter, David T.; Ward, Roberta J.
Abstract: Aim: To investigate pro-inflammatory markers in the blood and associate with cognitive impairment. Methods: Il-6 and ferritin were assayed in the blood of 27 patients, divided according to Lesch typology, at the commencement and after 21 days of detoxification, together with a battery of cognitive tests. Results: A significantly higher mean level of IL-6 was present in the blood of patients with Lesch typology 1 compared to the other typologies 2 and 3 on admission to the Detoxification Ward which did not alter significantly after detoxification. The mean level of IL-6 was initially elevated in Lesch typology 2 alcohol abusers and declined to the reference range after detoxification. Lesch typology 3 alcohol abusers showed normal levels of IL-6 at both time points. Only in Lesch typology 1 were the levels of ferritin and IL-10 significantly elevated at the start of the detoxification process. Cognitive impairment, as ascertained by Stroop test and Brown–Peterson procedure was greater in Lesch typology 1 than the other 2 patient groups. Conclusion: Such data might indicate a greater degree of neuroinflammation in Lesch typology 1 alcoholic patients. Short summary: Dividing a heterogeneous group of alcoholic subjects into homogenous groups according to Lesch typology, identifies a greater pro-inflammatory profile in Lesch typology 1 patients who also showed greater cognitive impairment.